THE Macrobrachium FISHERY OF THE LOWER TAYLOR CREEK, NIGER DELTA, NIGERIA - KINGDOM, T; ERONDU, E. S. (Nigerian Journal of Fisheries, 2012)
The Macrobrachium fishery of the Lower Taylor Creek was studied from June 2008 to May 2010. The aim was to present the status of Macrobrachium fishery in the Lower Taylor Creek with regard to catch rates and the socio - economics of the fishery. The fishers and traders involved in the shrimp business were extensively interviewed and samples were collected from the catches in the various towns along the creek. Macrobrachium fishing took place mainly between August and October each year. All the fishers/marketers were women. The fishing gear used in harvesting shrimps was the basket trap known locally as Ingo. Many women exercised customary access rights to the dugout channels (called ‘Adḛ’) where ‘Ingo’ traps were mostly placed during the fishing season. The catch rate (kg per trap and day) ranged from 0.01 ± 0.006kg (August 2008) to 0.079±0.006kg (October 2009). The catch rate (kg per canoe and day) was lowest in August 2009 (0.563±0.027kg) and highest in September 2009 (4.95±0.054kg). The mean price per kilogram of shrimp was estimated as N 795. 59k (1 US$ = N 152). The price of shrimps was always in the order August > September > October (P < 0.001). A fishing unit consisting of one canoe, a fisherwoman and several traps, was estimated to land 102.89kg of fresh shrimps, thereby fetching a gross income of N 81, 856. 66 (or $538. 53) per annum (using the mean price of N 795. 59k/kg of shrimps and 36 active fishing days per annum).